A Study of Patterns of Gender Representation and Job Performance among Academic Staff of Obafemi Awolowo University, Ile-Ife, Nigeria - Bola, ADENIYI Adijat; Olasunkanmi, ADENIYI Wasiu (Advances in Social Sciences Research Journal, 2015)
The thrust of this paper was to examine the gender representation vis-à-vis the perception of undergraduates toward the job performance of male and female academics. The study adopted both the survey and expo-facto research designs. A total of 987 undergraduates from Parts 2-4 were selected using convenience sampling technique from 10 randomly selected faculties from the Obafemi Awolowo University, lle-Ife, Nigeria. A self-developed instrument titled “Gender and Job Performance of Academic Staff” GJPA was used to collect information. Also, the information on academic staff strength of the university was obtained from the Budgeting and Planning Unit of the school (O.A.U., 2014). The instrument yielded test re-test reliability coefficient of r = 0.82 at 0.05 level of significance. The results showed that in 2010/2011 academic session, male academics accounted for 630(82%), while female academics had 134(18%). Tit was shown that in 2012/2013, 392(88%) of male academics were in senior ranks, while, 55(12%) of female academics were in senior ranks. Further, the results showed that there was no significant difference in the perception of undergraduates towards the academic competency of male and female academics (t = 0.083, p > 0.05). Lastly, the results showed that there was a significant difference in professional attainment of male and female academics (t-test = 0.667, p < 0.05). The study concluded even though male academic staff were more represented at the senior ranks and management positions, yet, this did not place them above their female counterparts when compared their academic competency.